Title not available in English. - Brito, Fausto (1995)
An essay about the International migrations in the capitalism development The essay makes an analysis in the history of the international migrations in the capitalism development. It compares the characteristics of the migrations during the so-called Second Industrial Revolution, in the second half of the last century, with those which have been happening in the present phase of the reorganization of the world economy, also known as the Third Industrial Revolution. If in the end of the XIX century and the beginning of the present one, the migrations from the center to the periphery were most likely to be permanent and the immigrants used to integrate in the countries of destination, nowadays the migratory reality has been distinct: fruit of the internalization of the job market and of the deep inequality among the nations, most of the migrations turn to be each day more temporary and the migrants, just laborers who circulate internationally.